2013
DOI: 10.1387/ijdb.130240qw
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent protein marker lines in maize: generation and applications

Abstract: Fluorescent proteins (FP) have significantly impacted the way that we study plants in the past two decades. In the post-genomics era, these FP tools are in higher demand by plant scientists for studying the dynamics of protein localization, function, and interactions, and to translate sequence information to biological knowledge that can benefit humans. Although FP tools have been widely used in the model plant Arabidopsis, few FP resources have been developed for maize, one of the most important food crops wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 101 publications
(112 reference statements)
1
27
0
Order By: Relevance
“…Interestingly, our results showed that the expression level of auxin-responsive genes was significantly higher in DSY2 as compared with DSY79, suggesting modulating auxin-signaling might be one strategy that DSY2 applied to cope with P-starvation. Therefore, further studies may focus on analyzing auxin distribution transport using the maize fluorescence-based reporter lines from the maize cell genomic resources1415. Besides the auxin, recent studies also report that the cell wall proteins expansins that regulate cell division and expansion rates may play a critical role in the root architecture responses to low-P stress1116.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our results showed that the expression level of auxin-responsive genes was significantly higher in DSY2 as compared with DSY79, suggesting modulating auxin-signaling might be one strategy that DSY2 applied to cope with P-starvation. Therefore, further studies may focus on analyzing auxin distribution transport using the maize fluorescence-based reporter lines from the maize cell genomic resources1415. Besides the auxin, recent studies also report that the cell wall proteins expansins that regulate cell division and expansion rates may play a critical role in the root architecture responses to low-P stress1116.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it cannot be ruled out that ZmLOX10 provides substrate towards JA biosynthesis during stress response in a tissue- or stimulus-specific manner. A cautionary note, careful examination of the subcellular localization of ZmLOX9-YFP, did not find it to be localized to chloroplasts [55]. …”
Section: 13-lipoxygenasesmentioning
confidence: 99%
“…In addition to these traditional genetic resources, there is a large collection of fluorescent protein marker lines (Mohanty et al 2009; Wu et al 2013). Among these is a suite of cell biological markers (tubulin, chromosomes, ER, cell wall, etc .)…”
Section: Chromosomes and Mutant Collectionsmentioning
confidence: 99%
“…These lines are being used in live-cell studies of cell division (Figure 3B) and, for example, to interpret the expression of a gene that suppresses branching (tillering) at the base of the plant thereby promoting the single-stalk growth pattern typical of agricultural corn (Whipple et al 2011). Two-component trans -activating fluorescent lines have also been generated for tissue-specific control of gene expression (Wu et al 2013). …”
Section: Chromosomes and Mutant Collectionsmentioning
confidence: 99%